Species Divergence vs. Functional Convergence Characterizes Crude Oil Microbial Community Assembly - Nie, Yong; Zhao, Jie-Yu; Tang, Yue-Qin; Guo, Peng; Yang, Yunfeng; Wu, Xiao-Lei; Zhao, Fangqing (Frontiers in Microbiology, 2016)
Oil reservoirs exhibit extreme environmental conditions such as high salinity and high temperature. Insights into microbial community assemblages in oil reservoirs and their functional potentials are important for understanding biogeochemical cycles in the subterranean biosphere. In this study, we performed shotgun metagenomic sequencing of crude oil samples from two geographically distant oil reservoirs in China, and compared them with all the 948 available environmental metagenomes deposited in IMG database (until October 2013). Although the dominant bacteria and the proportion of hydrogenotrophic and acetoclastic methanogens were different among oil metagenomes, compared with the metagenomes from other environments, all the oil metagenomes contained higher abundances of genes involved in methanogenic hydrocarbon degradation and stress response systems. In addition, a “shape-sorting” manner was proposed for the assembly of microbial communities in oil reservoirs, with the oil reservoir acting as a function sorter to select microbes with special functions from its endemic pool of microorganisms. At the functional level, we found that environmental metagenomes were generally clustered according to their isolation environments but not their geographical locations, suggesting selective processes to be involved in the assembly of microbial communities based on functional gene composition.